A new genus of predatory katydids (Orthoptera: Tettigoniidae: Listroscelidinae) from the Amazonian Rainforest - Mendes, Diego Matheus De Mello; Chamorro-Rengifo, Juliana; Rafael, José Albertino (Zootaxa, 2016)
Most of the predatory katydids Listroscelidini species known were described from the Brazilian Atlantic Forest. Here a new genus and species from the Amazonian Rainforest is described. Based on its morphological characteristics, this new genus represents an intermediate form between two closely related genera, Listroscelis Serville and Monocerophora Walker.